Limboto Lake Band Land Rights Arrangements - Junus, Nirwan; Mamu, Karlin Zakaria (Universitas Negeri Gorontalo, 2022)
This paper aims to examine the regulation of land use by the Limboto Lake community. This study uses an empirical juridical approach. The study results show that the regulation of land rights, especially land along the banks, has been regulated by the government and local governments, starting from laws and regulations, regional regulations, and other decisions. The existence of laws and regulations has given legitimacy to the state, in this case, the government, regarding the control and utilization of the land on the banks of the lake because the state legally owns the land on Lake Limboto. However, the fact is that the land on the banks of the lake has changed its function to become a community settlement. , making it difficult to carry out an inventory of the surrounding population. In order to prevent mismanagement or management that is not based on the rule of law, it is necessary to have clear and accurate boundaries regarding the allotment of areas/zones for various interests so that there is no overlap between the government and the land agency, considering that some community lands already have land rights (land certificate). Thus, an alternative solution to save the lake is establishing a zoning system.